Diagnosis Miskonsepsi Terhadap Konsep Hukum Newton dan Penerapannya pada Peserta Didik: Four-Tier Diagnotic Test - Sahara, Yuni; Erniwati, Erniwati; Sahara, La (Jurusan Pendidikan Fisika, 2019)
The purpose of this research is: (1) to get a description of the misconceptions of grade X students of SMKN 2 Kendari on the subject matter of Newton's law and its application; (2) shows the highest concept of misconception in Newton's law and its application. The research population as a sample was all students of class X in Electrical Engineering at SMKN 2 Kendari consisting of 2 classes of 56 people. Data collection in the research was a four-tier diagnostic test totaling 25 numbers and interviews. Interviews were conducted as a support to confirm the results of the tests that have been carried out. Data were analyzed qualitatively, from the results of the data analysis conclusions were obtained: (1) Misconceptions that occur in students after undergoing diagnostic tests are in the moderate categorized with a percentage of 39.07%. (2) The highest misconception was identified in Newton's first law material with a percentage of 47.32%, followed by Newton's legal application sub-concept 46.88%, Newton's II legal sub-concept 41.07%, Newton's 36 , 61%, Newton's third law sub concept 35.71% and the last sub-concept types of force 35.46%.